Association between Dietary Total Antioxidant Capacity and Odds of Preeclampsia: A Case-control Study - Mahshid Taherkhani; Farzaneh Montazerifar; Azita Hekmatdoost; Bahram Rashidkhani; Abolfazl Payandeh; Mansour Karajibani (Journal of Nutrition and Food Security)
Background: Preeclampsia may cause maternal and child morbidity and mortality. Evidence suggests that oxidative stress may be involved in the development of preeclampsia; however, the role of dietary total antioxidant capacity (DTAC) on preeclampsia risk has not yet been elucidated. Thus, this study aims to assess the relationship between DTAC and odds of preeclampsia. Methods: This case-control study was conducted on 240 pregnant women (preeclampsia, n=60; controls, n=180) in Qazvin, Iran. Controls were 3:1 ratio matched with cases in terms of participants’ age and gestational age. Dietary intakes were assessed using a validated food frequency questionnaire evaluating the preceding year. DTAC was measured by two methods: ferric reducing antioxidant potential (FRAP) and oxygen radical absorbance capacity (ORAC). Multivariable logistic regression was employed to evaluate the association between preeclampsia and DTAC and also selected antioxidants. Results: After controlling for potential confounders, a significant inverse relationship was found between ORAC and preeclampsia; individuals in the highest tertile of ORAC were 67% less likely to have preeclampsia than those in the lowest tertile of ORAC (OR: 0.33; 95% CI: 0.11-0.97; P-trend<0.05). There was no significant relation between FRAP and preeclampsia. The risk of preeclampsia was 70% lower among subjects with the highest tertile of vitamin C intake compared to the lowest tertile of it. Conclusion: Pregnant women with the highest tertile of ORAC and vitamin C intake were at lower risk of preeclampsia. Therefore, prospective studies are needed to confirm the protective effects of dietary anti-oxidants on preeclampsia incidence.